Dimensi Pengetahuan Dan Tingkat Berpikir Pada Pembelajaran Kimia - Nopriawan Berkat Asi (FKIP Universitas Palangka Raya, 2018)
The knowledge intended in the 2013 curriculum can be divided into 4 (four) dimensions of knowledge. Dimensions of knowledge include factual knowledge, conceptual knowledge, procedural knowledge and metacognitive knowledge. The purpose of this study is to discuss the dimensions of knowledge and the level of thinking in learning chemistry. The cognitive process in learning chemistry in high school is strived for students to be able to reach the level of critical thinking and be able to solve chemical problems that require critical thinking. Students who think critically in solving chemical problems are those who can apply procedural knowledge and metacognitive knowledge in solving certain chemical problems based on certain situations presented to them correctly and can show the key to solving problems. Critical thinking is a basic ability for the development of knowledge in learning chemistry. Students who get various concepts and contexts of chemical problems are expected to be able to successfully recognize paradoxes and solve chemical problems with their knowledge.